Density‐Dependence of Surface Transport in Tellurium‐Enriched Nanograined Bulk Bi2Te3. Issue 11 (15th January 2023) - Izadi, Sepideh; Bhattacharya, Ahana; Salloum, Sarah; Han, Jeong Woo; Schnatmann, Lauritz; Wolff, Ulrike; Perez, Nicolas; Bendt, Georg; Ennen, Inga; Hütten, Andreas; Nielsch, Kornelius; Schulz, Stephan; et al.
Abstract: Three‐dimensional topological insulators (3D TI) exhibit conventional parabolic bulk bands and protected Dirac surface states. A thorough investigation of the different transport channels provided by the bulk and surface carriers using macroscopic samples may provide a path toward accessing superior surface transport properties. Bi2 Te3 materials make promising 3D TI models; however, due to their complicated defect chemistry, these materials have a high number of charge carriers in the bulk that dominate the transport, even as nanograined structures. To partially control the bulk charge carrier density, herein the synthesis of Te‐enriched Bi2 Te3 nanoparticles is reported. The resulting nanoparticles are compacted into nanograined pellets of varying porosity to tailor the surface‐to‐volume ratio, thereby emphasizing the surface transport channels. The nanograined pellets are characterized by a combination of resistivity, Hall‐ and magneto‐conductance measurements together with (THz) time‐domain reflectivity measurements. Using the Hikami‐Larkin‐Nagaoka (HLN) model, a characteristic coherence length of ≈200 nm is reported that is considerably larger than the diameter of the nanograins. The different contributions from the bulk and surface carriers are disentangled by THz spectroscopy, thus emphasizing the dominant role of the surface carriers. The results strongly suggest that the surface transport carriers have overcome the hindrance imposed by nanoparticle boundaries. Abstract : Tellurium‐rich Bi2 Te3 nanoparticle are synthesized in an ionic liquid‐based approach. Highly porous Bi2 Te3 compacted bulk material is used facilitating surface transport. A phase coherence length in the order of 200 nm is calculated using quantum interference Hikami–Larkin–Nagaoka approach. Terahertz reflectance reveals major surface transport contribution at low frequencies with surface mobility of around 10 4 cm 2 V ‐1 S ‐1 at 4 K.